Government grant for athletic scholarships in the Federal District: economic profile, athletic information and academic status of the recipients - Felipe Rodrigues da Costa; Alexandre Luiz Gonçalves de Rezende; Fernando Bernardes Martins; Hugo Paula Almeida da Rocha; Antonio Jorge Gonçalves Soares (Colégio Brasileiro de Ciências do Esporte, 2022)
ABSTRACT This study outlined the profile of athletes participating in the Athlete Scholarship Program of the Federal District to conduct a processual analysis of factors composing the holistic dual career model. The research sample included 25 athletes who benefited from the program in 2014. Data were collected through an online structured questionnaire about the topic under discussion. The main results indicate that the athletes present no educational delay, have high educational expectations, and that most belong to the highest socioeconomic class. Sporting and educational institutions must stimulate the organization of public policies, increasing public investments in high performance sports.